Strawbery Meningkatkan High Density Lipoprotein pada Lansia Dislipidemia - Yase, I Made; Yosse, Gabriel; Chandra, Uray (Media Ilmu Kesehatan, 2012)
Background : Approaching the year 2020 cardiovascular disease will become the leadingcause of death in the world before the age of 65 years. National Health Survey in 2001 showedthat deaths due to cardiovascular diseases including coronary heart disease amountedto 26.4%, and until now CHD is also a major cause of premature death. Thus, responsibilityfor the disease is not only done by the medical worker but also every individual. Recentresearch suggests that increasing HDL cholesterol can prevent cardiovascular disease.Anthocyanins that are found in various plants Including strawberrie may reduce the risk ofcardiovascular disease.Purpose : to identify the effect of strawberry juice administration on levels of HDL in old peoplewith dyslipidemia.Methods : The study design used in this study is quasi experimental research (quasiexperiment) with the type of control group pretest-postest design that examines the influenceof strawberry juice on the levels of HDL in patients with dyslipidemia by measuringthe levels of HDL before treatment and after treatment. The population in this study were oldpeople with dyslipidemia aged 55-65 years old . The population is divided into two groups,which were the control group and test group. The control group did not receive anytreatment,while the test group consume strawberry juice for 14 days with a dose of 100g/day.Result : The results in each group obtained by calculating the average difference in thecontrol group and test group. In the control group decreased HDL cholesterol levels of 0.285mg / dl and in the test group there was an increase in HDL cholesterol of 24.582 mg / dl.Conclusion : Juice of strawberries which contain anthocyanin can increase levels of HDL inold people with dyslipidemia Keyword: Strawberries, HDL, dyslipidemia